Acute, transitional and long-term cluster headache treatment: pharmacokinetic issues. (1st September 2016) - de Andrés, Fernando; Lionetto, Luana; Curto, Martina; Capi, Matilde; Cipolla, Fabiola; Negro, Andrea; Martelletti, Paolo
ABSTRACT: Introduction : The cornerstones of cluster headache therapy are based on the tripod of acute, transitional and preventative treatments that respectively aim to the control of the bouts, the transitional suppression of the relapse and the prevention of the entire cluster period. Particularly in chronic cluster headache, where a long-term preventative therapy is necessary, multiple drug regimens increase the risk of drug-drug interactions leading to variability in the clinical efficacy and to potentially harmful adverse effects. Areas covered : We focused on how clinically significant pharmacokinetic drug-drug and food-drug interactions can be carefully managed both in cluster headache patients with a progressive frequency of bouts and in chronic cluster headache sufferers. In fact, in these cases a long-term preventive therapy is indicated, increasing the possibility of interactions both with other transitional and acute cluster headache medications and with other foods or xenobiotics. Expert opinion : Pharmacokinetic interactions for both preventive, transitional and acute drugs are significant with a number of xenobiotics and other medications. Therefore, the pharmacokinetic issues knowledge is advisable for a safe and effective cluster headache management.